Clinical profile of patients with secretory otitis media - Tadasadmath, Sanjeev Kumar; Mushtaq, Syed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Most affected by secretory otitis media are children who more often than not do often know that something is wrong with their ears. It is the most common hearing disorder in children starting mostly before school age. Affected ears harbor middle ear effusion which causes hearing, loss, but usually no other otologic symptoms. Methods: The fifty cases were chosen in different age group and sex, based on their symptoms, and confirmed by otoscopic finding and pure tone audiometry. And these were further studied in detail as per the proforma enclosed. Results: On otoscopic examination the predominant sign was the prominence of handle of malleus and short process, flashing movement of the tympanic membrane. The tympanic membrane was found as full, lusterless and amber coloured. Conclusions: Secretory otitis media can be diagnosed clinically to the accuracy of 90%.